Design for Directorate of Health in Nablus - Resha, Ahmad; Khouerh, Osama; Abu Raad, Qusai (My University, 2018)
Since 1994, the PNA and private health sector enhanced the public system of health care, resulting in good health statistics throughout the last 20 years. The Palestinian Ministry of Health aims to ensure providing high quality, safe and sustainable health services within the available resources and fair service delivery to all citizens. The Directorate of Health building in Nablus includes many facilities that mainly provide medical services to the citizens. These facilities include sections like Pharmacy, Thalassemia Lab and Clinical rooms. And there are some other services like health insurance transactions, maternity care and childhood and other services. The main goal of this project was to design an integrated Directorate of Health building which was fully structurally safe and environmentally comfortable. To achieve this goal an order steps and tasks were taken through this process. The tasks spread in two levels, one in each semester. In the first semester, all information about directorates of health were collected by doing a literature review through reading books related to the subject, site visits, meetings and discussions with staff of different levels, analyze and evaluate the site concerning orientation, wind direction and other factors. Finally, analyze and evaluate the Electro-Mechanical system in the building and knew the level of comfort in it. For the second semester, the steps began with analysis of the site on which DOH intended to be constructed regarding to its topographical nature of land and surrounding environment. Then the integrated design of the building connected to architectural design including spaces and orientation, and environmental design including ventilation, lighting and acoustics systems. As for structural design, it included firstly the analysis of the 3D model of the building, soil-structure interaction and seismic analysis then came the design process using a computer software. The HVAC, water, and sanitary systems were designed throughout the mechanical design stage. The electrical design was introduced including lighting and power systems and control panel design. Also, emergency exits and an alarm system were also included in the public safety design. Finally, tender documents were prepared attached to the report which contain design details, bills of quantities and cost estimate.